Cracking your genetic code [videorecording (DVD)] - Holt, Sarah; Holt, Sarah; Holt, Sarah (PBS Distribution, 2012)
What will it mean when most of us can afford to have the information in our DNA, all six billion chemical letters of it, read, stored and available for analysis? Reveals that we stand on the verge of such a revolution. Meet a cancer patient who appears to have cheated death and a cystic fibrosis sufferer breathing easily because scientists have been able to pinpoint and neutralize the genetic abnormalities underlying their conditions.